2019
DOI: 10.21203/rs.2.16207/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative analyses of gene expression profile reveal potential crucial roles of mitotic cell cycle and microtubule cytoskeleton in pulmonary artery hypertension

Abstract: Background: Pulmonary arterial hypertension (PAH) is a life-threatening condition that gets worse over time. Despite advances in the development of strategies for treating PAH, prognosis of the disease remains unsatisfactory, especially for advanced PAH. The aim of this study was to explore potential crucial genes and pathways associated with PAH that can be used as potential biomarkers for early diagnosis.Results: Gene expression profile of pulmonary tissues from 27 PAH patients and 22 normal controls were do… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The Comparative Toxicogenomics Database (CTD) (https://ctdbase.org) is an important public resource database based on literature, 13 which is used to search for the interactions among chemical substances, genes, phenotypes, diseases and environments. In the database, inference scores were calculated based on the original documents to show the relationship between genes and diseases.…”
Section: Ctd Database Verified Ssc Related Degsmentioning
confidence: 99%
“…The Comparative Toxicogenomics Database (CTD) (https://ctdbase.org) is an important public resource database based on literature, 13 which is used to search for the interactions among chemical substances, genes, phenotypes, diseases and environments. In the database, inference scores were calculated based on the original documents to show the relationship between genes and diseases.…”
Section: Ctd Database Verified Ssc Related Degsmentioning
confidence: 99%
“…ere has been a number of PAH studies using microarray analyses [17][18][19], and the signaling pathway or hub genes identified by each study varied widely.…”
Section: Discussionmentioning
confidence: 99%
“…By integrated bioinformatical analysis, Luo et al found that the mitotic cell cycle is the crucial biological process dealing with pathogenesis of PAH, and they identified five key genes ( CDK1 , SMC2 , SMC4 , KIF23 , and CENPE ) which are involved in cell cycle progression. They further found that the predicted miRNAS targeting these hub genes were enriched in TGF‐β signalling 72 . It was found that pulmonary vascular remodelling in animal models could be attenuated or prevented by inhibiting TGF‐β signalling pathway, 73,74 and another study using osthole, a bioactive coumarin derivative extracted from Cnidium monnieri (L.) Cusson seeds, found that osthole significantly induced cell cycle arrest at the G0/G1 phase in PASMCs, and these effects might be partly related to the downregulation of the TGF‐β signalling activity 75 …”
Section: Pulmonary Vasculature Senescence and Pulmonary Arterial Hype...mentioning
confidence: 97%
“…They further found that the predicted miRNAS targeting these hub genes were enriched in TGF-β signalling. 72 It was found that pulmonary vascular remodelling in animal models could be attenuated or prevented by inhibiting TGFβ signalling pathway, 73,74 and another study using osthole, a bioactive coumarin derivative extracted from Cnidium monnieri (L.) Cusson seeds, found that osthole significantly induced cell cycle arrest at the G0/G1 phase in PASMCs, and these effects might be partly related to the downregulation of the TGF-β signalling activity. 75…”
Section: Tgf-β Signallingmentioning
confidence: 99%